Socialization & Education on the Participation of High School Students as Young Citizens in Facing the Implementation of the 2024 Simultaneous Elections - Kariadi, Dodik; Suprapto, Wasis; Fitriyadi, Slamat; Wirawan, Gunta; Kamaruddin, Kamaruddin; Utama, Erdi Guna (STKIP Singkawang, 2023)
In order to welcome the holding of simultaneous general elections which will be held in 2024, community service activities (PPM) carried out at SMA Negeri 1 Singkawang City are carried out with the aim that students as potential novice voters in 2024 can be more educated and knowledgeable in order to succeed in the democratic arena in Indonesia. This community service is carried out by visiting SMA Negeri 1 Singkawang City to carry out education and socialization so that class XII students as potential novice voters know their roles and responsibilities as citizens. Educational and outreach efforts are carried out by presenting teaching aids on how to channel political rights during the simultaneous general elections in the upcoming 2024 period. The impact to be obtained from PPM is that students have more awareness and understanding of the importance of their participation in channeling their political aspirations for the first time in general elections. Referring to the overall results of the dedication, the suggestion for schools is to form a forum in the form of extracurriculars that houses students who have more interest in politics so that their abilities in this field can be honed from an early age